Model Penjadwalan Pengiriman Pasokan pada Strategi Multi-Supplier dengan Variasi Harga dan Lead Time untuk Permintaan Stokastik - Nur Aini Masruroh; Anggita Virgiana Prasetyorini (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2015)
Multi-supplier is one of the strategies to minimize holding cost and average stock-out cost as long as to stabilize the supply of raw materials. The common problems that the firms may face when applying the multi-supplier strategy are determining the right schedule and quantity ordered for each supplier. Complexity of the problem increases with the facts that each supplier may have different parameters, demand is uncertain, and the firms’ constraints. Thus, this research is done to answer two main objectives: (1) to determine the optimum safety time (minimum raw material inventory) to prevent the stockout due to the demand uncertainty and (2) to determine the right schedule and quantity ordered for each supplier considering the different suppliers parameters: price, lead time, and supply capacity. The problem is modeled in Mixed Integer Linear Programming with total minimum inventory cost as the objective. With the aim of testing the model, a case of multinational company that apply the multi-supplier strategy is used.